Turi kumwe (we are together) : a transdisciplinary exploration of the Burundian specialty coffee sector and its sustainability challenges - Rosenberg, Lauren Liesl (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2017.